THE ROLE OF THE STATE ADDRESS VIOLENCE IN SOCIAL CONFLICTS IN PERU - Ramón Ruffner, Jeri Gloria (2012)
The current social situation that exists today in Peru reveal various recurring problems that for decades have not been resolved and have resulted on the so-called Social Conflicts. Some of the causes can be summarized as unsatisfied basic needs, limited participation in the public life of the most vulnerable groups, lack of mechanism to raise estate policy that allows appropriate distribution of resources and a lack of mechanism to make demands. There is a need for new and creative ways to approach these problems. We need working solutions that are sustainable over time. One of the basic conditions for the country’s governability is the implementation of effective policies that are aimed at achieving equity and inclusion, which will also contribute to the promotion of investment and decentralization. In this context, appropriate and effective intervention in the management of social conflicts is essential. Thus, this article aims to analyze the dimensions of social conflict, and highlight the role of the state and its legal competence to such conflicts.